Correction: Integrated Analysis of Environment, Cattle and Human Serological Data: Risks and Mechanisms of Transmission of Rift Valley Fever in Madagascar. - Marie-Marie Olive; Véronique Chevalier; Vladimir Grosbois; Annelise Tran; Soa-Fy Andriamandimby; Benoit Durand; Jean-Pierre Ravalohery; Seta Andriamamonjy; Fanjasoa Rakotomanana; Christophe Rogier; Jean-Michel Heraud (Public Library of Science (PLoS), 2016)
[This corrects the article DOI: 10.1371/journal.pntd.0004827.].